2023
DOI: 10.1002/jsfa.12817
|View full text |Cite
|
Sign up to set email alerts
|

Air speed and plastic crate vent‐holes for wine grape quality during postharvest dehydration: commercial and laboratory studies

Abstract: BACKGROUNDAirflow is an important issue to favor postharvest dehydration keeping wine grape quality. The aim of this experimental work was to analyze the grape quality during postharvest dehydration: (i) in a commercial facility (‘fruttaia’) by monitoring the efficiency of the ventilation system and (ii) at laboratory level, studying the influence of crate type and airflow direction.RESULTSIn the fruttaia, the airflow was provided by an air duct hanging from the ceiling, and by floor fans. A great gap in air s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The pomace used, on the other hand, was grapes cv Aleatico ( Vitis Vinifera L.) manually harvested in September 2021, at the Fattoria di Calappiano (Sensi Vigne & Vini, Lamporecchio, Italy). The bunches were placed in perforated plastic crates for the dehydration process in a ventilated tunnel (temperature = 20 ± 2 °C; humidity = 65 ± 3 °C; airflow = 1 m/s; time = 20 days), up to 40% of weight loss [ 17 ]. At the end, the bunches were pressed with a pneumatic press 40 L (Polsinelli Enologia Srl, Isola del Liri, Italy), and the pomace, left over from the juice extraction, was used in the production of IGA-P beer.…”
Section: Methodsmentioning
confidence: 99%
“…The pomace used, on the other hand, was grapes cv Aleatico ( Vitis Vinifera L.) manually harvested in September 2021, at the Fattoria di Calappiano (Sensi Vigne & Vini, Lamporecchio, Italy). The bunches were placed in perforated plastic crates for the dehydration process in a ventilated tunnel (temperature = 20 ± 2 °C; humidity = 65 ± 3 °C; airflow = 1 m/s; time = 20 days), up to 40% of weight loss [ 17 ]. At the end, the bunches were pressed with a pneumatic press 40 L (Polsinelli Enologia Srl, Isola del Liri, Italy), and the pomace, left over from the juice extraction, was used in the production of IGA-P beer.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, several studies have linked Si with elevated shoot and root activities of antioxidants, both enzymatic (e.g., superoxide dismutase, peroxidase, catalase, ascorbate peroxidase and glutathione reductase) and non-enzymatic (e.g., ascorbate, glutathione, phenolic compounds, etc. ), as well as changes in the concentrations of common markers of oxidative stress, including malondialdehyde, hydrogen peroxide (H 2 O 2 ) and proline, under various abiotic stresses [68,69].…”
Section: Enzymatic Activitymentioning
confidence: 99%
“…1 O 2 increases towards the central axis corresponding to the presence of air spaces that are connected to the pedicel where lenticels are located, which are important for berry O 2 uptake as a function of temperature; when lenticels are blocked, a hypoxia condition starts in grape berries, as well as ethanol accumulation and CD. [2][3][4] Xiao et al 5 demonstrated that, in non-irrigated vines, berry O 2 decreased, whereas both CD and ethanol concentration increased. Water stress is the typical stress occurring during postharvest wine grape dehydration, which induced great changes in terms of metabolism.…”
Section: Introductionmentioning
confidence: 99%